2020
DOI: 10.7554/elife.44525
|View full text |Cite
|
Sign up to set email alerts
|

The carboxyl-terminal sequence of bim enables bax activation and killing of unprimed cells

Abstract: The Bcl-2 family BH3 protein Bim promotes apoptosis at mitochondria by activating the pore-forming proteins Bax and Bak and by inhibiting the anti-apoptotic proteins Bcl-XL, Bcl-2 and Mcl-1. Bim binds to these proteins via its BH3 domain and to the mitochondrial membrane by a carboxyl-terminal sequence (CTS). In cells killed by Bim, the expression of a Bim mutant in which the CTS was deleted (BimL-dCTS) triggered apoptosis that correlated with inhibition of anti-apoptotic proteins being sufficient to permeabil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 50 publications
1
46
0
Order By: Relevance
“…Bim not only inhibits anti-apoptotic proteins it also activates the executioner proteins Bax and Bak, potentially confounding analysis. As this mechanism may be relevant in multiple cell lines it is examined in more detail elsewhere ( Chi et al, 2019 ). Second, MCF-7 cells depend on MCL-1 for survival ( Figure 3E ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bim not only inhibits anti-apoptotic proteins it also activates the executioner proteins Bax and Bak, potentially confounding analysis. As this mechanism may be relevant in multiple cell lines it is examined in more detail elsewhere ( Chi et al, 2019 ). Second, MCF-7 cells depend on MCL-1 for survival ( Figure 3E ).…”
Section: Resultsmentioning
confidence: 99%
“…Purified Bcl-XL and BimL protein binding in the presence of different concentrations of ABT-263 quantified in vitro using purified full-length proteins with ( D ) and without ( E ) liposomes. Control experiments demonstrating efficient binding of BimL to liposomes and Bcl-XL binding data for the Bim mutants are presented in the companion paper ( Chi et al, 2019 ). Data are mean ±SD (n = 3 independent experiments).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, primary cultures of murine hippocampal neurons taken at the embryonic stage develop resistance to apoptotic stimuli as they mature in vitro [21]. Furthermore, we have observed that mature cultures of primary cortical neurons resist death in response to the expression of truncated BIM, a protein with reduced pro-apoptotic activity [22]. However, these cultures of mature neurons remain sensitive to the expression of full-length BIM, demonstrating that mature neurons are resistant, but not entirely refractory to apoptotic stimuli [22].…”
Section: Neuronal Cell Death and Axon Degeneration In Developmentmentioning
confidence: 91%
“…Furthermore, we have observed that mature cultures of primary cortical neurons resist death in response to the expression of truncated BIM, a protein with reduced pro-apoptotic activity [22]. However, these cultures of mature neurons remain sensitive to the expression of full-length BIM, demonstrating that mature neurons are resistant, but not entirely refractory to apoptotic stimuli [22]. Resistance to apoptotic stimuli correlating with the maturation of neurons has also been shown in vitro with cultures of sympathetic neurons of the PNS [23][24][25].…”
Section: Neuronal Cell Death and Axon Degeneration In Developmentmentioning
confidence: 99%